Organización contable en la empresa comercial “Pollo Lojano” de la Sra. Johanna Elizabeth Malo Romero de la ciudad de Loja, periodo del 01 de abril al 30 de junio del 2023 - Malo Balvuca, Stefanny Lizbeth (2024)
The curricular or degree integration work called: Accounting organization in the commercial company “Pollo Lojano” of Mrs. Johanna Elizabeth Malo Romero of the city of Loja, period from April 1 to June 30, 2023, the present study was carried out as part of the requirements to obtain the degree and title of Bachelor of Accounting and Auditing, its main purpose was to determine the economic and financial situation of the company, using the results obtained from the accounting process implemented. In the first objective, the development of a plan and account manual according to the needs of the company was carried out, establishing a list with the purpose of distinguishing the different codifications. In the second objective, auxiliary records were prepared, which provided detailed information. On the financial transactions carried out during the period, the data was collected, classified and recorded using the source documents as a reference. The third objective allowed us to begin the preparation of the Initial Inventory, the initial state of affairs, to record the economic activities through the registration of the accounting entries in the Journal, in such a way this information was consolidated in the ledgers, which which produced the Trial Balance and the Worksheet with the pertinent adjustments, concluding with the preparation of the Financial Statements through proper management, in which the Statement of Financial Situation could show a total of assets of $125,348.01, liabilities of $1,441.38 and assets of $123,906.63; The Income Statement shows income of $72,029.65, costs of $61,626.37 and expenses of $64,770.44, resulting in a net profit for the year of $7,259.21, and the Cash Flow Statement reflected a balance of $26,978.83. Analysis of the Cost of Product Sold Statement allowed us to determine the total value of the poultry product throughout the financial year and, consequently, displaying the cost of product sold of $62,707.68.